2013
DOI: 10.2478/s13380-013-0141-2
|View full text |Cite
|
Sign up to set email alerts
|

Grey and white matter brain network changes in frontotemporal dementia subtypes

Abstract: Grey and whIte matter braIn network chanGes In frontotemporal dementIa subtypes abstract Background: Frontotemporal dementia (FTD) comprises of three clinical syndromes, behavioural-variant frontotemporal dementia (bvFTD), semantic dementia (SV-PPA), and progressive nonfluent aphasia (NFV-PPA) with unique underlying neuroanatomical deficits. To date, however, grey matter structural differences and their connecting white matter tracts in this network have been mostly characterised in comparison to controls, whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 49 publications
(44 reference statements)
1
2
0
Order By: Relevance
“…Moreover, the functional graph theory models captured node-degree differences in the left superior occipital area ( Agosta et al, 2013 ; Reyes et al, 2018 ), left Heschl gyrus ( Agosta et al, 2013 ), and left frontal inferior pars triangularis ( Zhou et al, 2012 ). Regarding the raw structural connectivity models, and in agreement with previous research, we found alterations in the uncinate fasciculus ( Agosta et al, 2012 ; Daianu et al, 2016 ; Iaccarino et al, 2015 ; Nguyen et al, 2013 ), superior longitudinal fasciculus ( Agosta et al, 2012 ; Daianu et al, 2016 ), corpus callosum ( Tovar-Moll et al, 2014 ), dentatorubrothalamic tract ( Whitwell et al, 2011a ), and inferior fronto-occipital fasciculus ( Meijboom et al, 2017 ). Second, adding cognitive features (i.e., multifeatured approach) increased the averaged AUC performance metrics across all subject groups.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the functional graph theory models captured node-degree differences in the left superior occipital area ( Agosta et al, 2013 ; Reyes et al, 2018 ), left Heschl gyrus ( Agosta et al, 2013 ), and left frontal inferior pars triangularis ( Zhou et al, 2012 ). Regarding the raw structural connectivity models, and in agreement with previous research, we found alterations in the uncinate fasciculus ( Agosta et al, 2012 ; Daianu et al, 2016 ; Iaccarino et al, 2015 ; Nguyen et al, 2013 ), superior longitudinal fasciculus ( Agosta et al, 2012 ; Daianu et al, 2016 ), corpus callosum ( Tovar-Moll et al, 2014 ), dentatorubrothalamic tract ( Whitwell et al, 2011a ), and inferior fronto-occipital fasciculus ( Meijboom et al, 2017 ). Second, adding cognitive features (i.e., multifeatured approach) increased the averaged AUC performance metrics across all subject groups.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, model performance may be lower. However, the multimodal approach helps to provide information on specific functional and structural alterations capturing differential patterns in FTD ( Agosta et al, 2012 ; Nguyen et al, 2013 ; Reyes et al, 2018 ; Whitwell, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The regions were selected based on known functions of different parts of the brain and the published structural MRI studies which had objectives comparable to our study. Many of these studies have described significant GM volume loss in frontal, insula, anterior cingulate, caudate, putamen, thalamus and temporal polar regions in bvFTD (27,28,29) and predominant temporal (temporal pole, anterior hippocampus) and extra temporal (ventromedial prefrontal cortex, insula, anterior cingulate, caudate) regions in PPA. (28,30,31) Hence, the ROIs drawn on both hemispheres taking the help of e-anatomy of IMAIOS (https://www.imaios.com/en/e-Anatomy/Head-and-Neck/Brain-MRI-3D) and included: the GM at the precentral gyrus (PCG) just anterior to central sulcus, adjacent subcortical WM and CSF in the central sulcus, superior frontal gyrus (SFG) medial to superior frontal sulcus, temporal pole (TP), Insula (IN), basal ganglia regions(caudate(CAU), putamine (PUT), globus pallidus (GP), substantia nigra (SN), red nucleus (RN), frontal WM (FWM), anterior cingulate (AC), defined by the grey matter abutting and posterior to the cingulate sulcus along with adjacent medial frontal lobe, hippocampus (HP) that included its head and body, and finally, dentate nucleus (DN) (Supplementary Figure 1).…”
Section: Methodsmentioning
confidence: 99%